The challenges of journal marketing and distribution in a developing economy (2005)
Developing countries face enormous social, political and economic problems in addition to being consumer economies that rely almost absolutely on importation. The knowledge production enterprise (in general) and the library and information science (LIS) profession (in particular) suffer due to inadequate media to communicate scholarly works in Nigeria. This paper identifies short lifespan, irregular issues of locally produced journals, and inability to sustain subscription to foreign ones as major shortcomings of LIS journal marketing in Nigeria. It posits that journal sustainability is mainly based on the returns made from journal marketing and distribution. However, the ability of institutions to subscribe to reputable journals is dependent on how well funded they are and every academic relies on the meager monthly allowance s/he earns which is hardly enough to personally subscribe to one good local journal. Moreover, the content and physical qualities of the journals also affect the extent of their marketing and distribution. The cumulative effect of these limitations is the pauperization of the knowledge industry through the unavailability of quality media for communicating research results and limited exposure to foreign research findings. The paper suggests, among other things, that Nigerian Library Association (NLA) and other stakeholders in the librarianship profession should create a regulatory body that would be responsible for setting standards, vetting the quality of, and endorsing journals produced, marketed and distributed in Nigeria